SEASONALITY OF MOOD AND BEHAVIOR IN THE OLD ORDER AMISH - Raheja, Uttam K. (2012)
BACKGROUND/OBJECTIVE: We examined seasonality and winter seasonal affective disorder (SAD) in the Old Order Amish of Lancaster County, Pennsylvania, a unique population that prohibits use of network electric light in their homes. METHODS: We estimated SAD using the Seasonal Pattern Assessment Questionnaire (SPAQ) in 1,306 Amish adults and compared the frequencies of SAD and total SAD (i.e., presence of either SAD or subsyndromal-SAD) between men and women, young and old, and awareness of (ever vs. never heard about) SAD. Heritability of global seasonality score (GSS) was estimated using the maximum likelihood method, including a household effect to capture shared environmental effects. RESULTS: The mean (± SD) GSS was 4.36 (± 3.38). Prevalence was 0.84% (95% CI: 0.36 – 1.58) for SAD and 2.59% (95% CI: 1.69 – 3.73) for total SAD. Heritability of GSS was 0.14 ± 0.06 (SE) (p = 0.002) after adjusting for age, gender, and household effects. LIMITATIONS: Limitations include likely overestimation of the rates of SAD by SPAQ, possible selection bias and recall bias, and limited generalizability of the study. CONCLUSIONS: In the Amish, GSS and SAD prevalence were lower than observed in earlier SPAQ-based studies in other predominantly Caucasian populations. Low heritability of SAD suggests dominant environmental effects. The effects of awareness, age and gender on SAD risk were similar as in previous studies. Identifying factors of resilience to SAD in the face of seasonal changes in the Amish could suggest novel preventative and therapeutic approaches to reduce the impact of SAD in the general population.